2014
DOI: 10.1055/s-0034-1376967
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 Beta (IL1beta) Gene Polymorphisms (SNP-511 and SNP+3953) in Hashimoto’s Thyroiditis among the Polish Population

Abstract: An association between the SNPs of the IL1 beta and susceptibility to Hashimoto's thyroiditis among the group of Caucasian-Polish population studied was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The findings are in agreement with the study of Zaaber et al, suggesting a significant relation between IL-1β rs1143634 SNP and GD and HT in the Tunisian population [27]. Lacka et al and Rashad et al also found a significant relationship between IL-1β rs1143634 SNP and HT in a Polish and Egyptian population, respectively [36,37]. In contrast, Chen et al found no association between IL-1β rs1143634 SNP and GD risk in Taiwan [38], while Liu et al found a positive relationship between the C allele of rs1143634 and GD risk [39].…”
Section: Discussionsupporting
confidence: 92%
“…The findings are in agreement with the study of Zaaber et al, suggesting a significant relation between IL-1β rs1143634 SNP and GD and HT in the Tunisian population [27]. Lacka et al and Rashad et al also found a significant relationship between IL-1β rs1143634 SNP and HT in a Polish and Egyptian population, respectively [36,37]. In contrast, Chen et al found no association between IL-1β rs1143634 SNP and GD risk in Taiwan [38], while Liu et al found a positive relationship between the C allele of rs1143634 and GD risk [39].…”
Section: Discussionsupporting
confidence: 92%
“…We did not assess polymorphisms, but the higher concentrations of selected cytokines may indicate that the genetic factors responsible for their production are of great importance in Hashimoto's disease. This has also been suggested by other Polish researchers [14]. IL-1β is released by peripheral blood monocytes, stimulates T lymphocytes to synthesize other proinflammatory cytokines, and affects the proliferation and differentiation of B lymphocytes.…”
Section: Discussionsupporting
confidence: 71%
“…Other parameters determined in this study were IL-1β [ 48 , 49 , 50 ] and IL-17 [ 42 , 51 , 52 ], which are associated with the pathogenesis of HT. In the study of Phenekos et al, the level of IL-1β in the serum of patients with HT at different stages of disease (TSH > 8 μIU/mL; some participants were treated with L-T 4 for up to 18 months) was significantly lower than in the group of healthy subjects (2.52 ± 0.14 vs. 3.6 ± 0.20 pg/mL) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%